Deterring democracy - Chomsky, Noam (London, 1992)
From World War II until the 1980s, the United States reigned supreme as both the economic and the military leader of the world. The major shifts in global politics that came about with the dismantling of the Eastern Bloc have left the United States unchallenged as the pre-eminent military power, but American economic might has declined drastically in the face of competition, first from Germany and Japan and more recently from the newly prosperous countries elsewhere.
Keywords: Democracy